Analisis Pertumbuhan Penjualan dan Return On Asset Terhadap Harga Saham Pada Perusahaan Otomotif dan Komponen yang Terdaftar di BEI Periode 2017-2023 - Septa Anggraeni; Titing Suharti; Diah Yudhawati (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to determine the effect of sales growth and return on assets on stock prices in automotive and component companies listed on the IDX for the period 2017-2023. The data collection technique used in this research is using the documentation method and the literature method. The data analysis method used in this research is panel data multiple regression analysis technique. The population in this study were 14 automotive and component companies listed on the IDX, the sample results that met the sample withdrawal criteria with the purposive sampling method in this study were 6 automotive and component companies listed on the IDX. The results of this study state that partially sales growth has no significant effect on stock prices. Return on assets has a significant effect on stock prices. Sales growth and return on assets simultaneously have a significant effect on stock prices.